2015
DOI: 10.1038/ncomms9371
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NKT cell-mediated immune responses to tumours and liver inflammation by mitochondrial PGAM5-Drp1 signalling

Abstract: The receptor-interacting protein kinase 3 (RIPK3) plays crucial roles in programmed necrosis and innate inflammatory responses. However, a little is known about the involvement of RIPK3 in NKT cell-mediated immune responses. Here, we demonstrate that RIPK3 plays an essential role in NKT cell function via activation of the mitochondrial phosphatase phosphoglycerate mutase 5 (PGAM5). RIPK3-mediated activation of PGAM5 promotes the expression of cytokines by facilitating nuclear translocation of NFAT and dephosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 60 publications
4
113
3
Order By: Relevance
“…Consistently, Ripk3 -/-mice developed ConA-induced hepatitis as severe as control mice. Accordingly, we observed only low basal levels of RIPK3 in hepatocytes, and similar to other reports (19,43), RIPK3 positivity was rather limited to nonparenchymal cells, particularly Kupffer cells. Although we have previously shown that RIPK3 is upregulated in intestinal epithelial cells undergoing TNF-α-triggered necroptosis (8), we were unable to detect induction of RIPK3 mRNA or protein in hepatocytes during the course of experimentally induced hepatitis or in human AIH.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Consistently, Ripk3 -/-mice developed ConA-induced hepatitis as severe as control mice. Accordingly, we observed only low basal levels of RIPK3 in hepatocytes, and similar to other reports (19,43), RIPK3 positivity was rather limited to nonparenchymal cells, particularly Kupffer cells. Although we have previously shown that RIPK3 is upregulated in intestinal epithelial cells undergoing TNF-α-triggered necroptosis (8), we were unable to detect induction of RIPK3 mRNA or protein in hepatocytes during the course of experimentally induced hepatitis or in human AIH.…”
Section: Discussionsupporting
confidence: 73%
“…Although we have previously shown that RIPK3 is upregulated in intestinal epithelial cells undergoing TNF-α-triggered necroptosis (8), we were unable to detect induction of RIPK3 mRNA or protein in hepatocytes during the course of experimentally induced hepatitis or in human AIH. In line with this, a recent study demonstrated that RIPK3 expression in hepatocytes is dispensable for inflammatory liver injury (43).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Additionally, receptor-interacting protein kinase -1 and -3 (RIPK1/3)-dependent and lipopolysaccharide (LPS)-dependent inflammasome activation, and cytokine production upon viral infection, requires Drp1-dependent mitochondrial fission to induce mitochondrial damage and generate ROS [186,187]. The mitochondrial phosphatase phosphoglycerate mutase 5 (PGAM5) is the mediator of such RIPK-dependent Drp1 activation [188]. Similarly, microglial cells (MCs) in the central nervous system require Drp1-driven mitochondrial fragmentation and ROS signalling for correct cytokine production [189] ( Fig.…”
Section: Inflammationmentioning
confidence: 99%
“…showed that deletion of Ripk3 in myeloid cells, but not hepatocytes, protected mice against ConA toxicity (20). Some of the discrepancies among these reports may be due to off-target effects of inhibitors, the dose of inhibitors and ConA used, strain-specific variations in the mice, and inconsistency in the use of littermate controls.…”
Section: 7mentioning
confidence: 76%